Stock market fluctuations of the actions of peruvian mining companies during the state of national emergency due to the effect of COVID-19 - Ordinola Valdez, Andrea Carmen Lidia (2021)
The objective of the work was to describe the repercussions that have been arising from the State of Nacional Emergency due to the effects of the coronavirus on the actions of Peruvian mining companies. The research was a quantitative approach, of an explanatory (causal) level, based on the quantification and econometric analysis of the time series of financial assets listed on the Lima Stock Exchange, focusing on the quarantine period that began on March 16 and ended on June 30, 2020, and its post-quarantine behavior. The selected sample was made up of representative mining companies that are in the top ten of the most important nationally. It is concluded that the profitability of mining companies listed on the Lima Stock Exchange, in the period studied, has been negative.